A comprehensive methodology to study double emulsion stability - Leister, Nico; Götz, Vanessa; Bachmann, Stephan Jan; Nachtigall, Stephanie; Hosseinpour, Saman; Peukert, Wolfgang; Karbstein, Heike (Journal of Colloid and Interface Science, 2022)
The stability of emulsions requires the fast formation of viscoelastic interfaces between water and oil phases. In double emulsions, two surfactant types (hydrophilic and lipophilic) are present and two interfacial films are involved. Understanding cooperative adsorption of these surfactants and its implication on properties of water/oil/water interfacial films will enable replacing the empirical methodologies used in designing double emulsion systems with a knowledge-based approach. The distribution of surfactants between the water/oil interfaces was investigated using single droplet diffusion experiments and simulation of equilibrium surfactant density profiles. The stability of the interfaces against coalescence was characterized by dye transport in a leach cell and coalescence time of single droplets in a model experiment. The conformation of the surfactants at an interface was then examined via surface rheology, sum frequency generation spectroscopy, and dissipative particle dynamics simulation. Two selected hydrophilic surfactants combined with a lipophilic surfactant induce very different properties at water/oil interfaces and different dye release behaviour from their corresponding double emulsions. Competitive adsorption of sodium dodecyl sulfate and lipophilic surfactant results in the improvement of encapsulation efficiency, elasticity of the interface, and resistance against coalescence due to the intercalation of surfactant alkyl chains into the oil chains.
Keywords: Coalescence; Diffusion; Double emulsions; Stability; Surfactants

Effect of surfactants on the molecular structure of the buried oil/water interface - Hosseinpour, Saman; Götz, Vanessa; Peukert, Wolfgang (Angewandte Chemie International Edition, 2021)
The oil/water interface, for instance in emulsions, is often stabilized by surfactants. Hence, the co-existence of oil, water, and surfactant molecules at the buried oil/water interface determines macroscopic properties such as surface tension or emulsion stability. Utilizing an inherently surface sensitive spectroscopic method, sum frequency generation (SFG) spectroscopy, we show that adsorption of an anionic surfactant to the buried oil/water interface increases the magnitude of the interfacial electric field. Meanwhile, the degree of ordering of the interfacial oil molecules increases with the surfactant concentration due to the intercalation of aliphatic chains of interfacial oil and surfactant molecules. At sufficiently high surfactant concentrations, the interfacial charge reaches a maximum value and the interfacial oil molecules arrange in a fully ordered conformation, a state which coincides with the significant decrease in interfacial tension and increased emulsion stability.